2012
DOI: 10.4103/0975-3583.95362
|View full text |Cite
|
Sign up to set email alerts
|

Family history of type 2 diabetes and prevalence of metabolic syndrome in adult Asian Indians

Abstract: Background:Our objective was to test the association between familial risk of type 2 diabetes mellitus (T2DM) and the prevalence of metabolic syndrome (MS) in adult Asian Indians.Materials and Methods:A total of 448 adult (>30 years) individuals (257 males and 191 females) participated in the study. Familial risk of T2DM was classified into three groups viz., 1=both parents affected; 2=parent and/or siblings affected and 3=none or no family history for T2DM. Anthropometric measures, blood pressures, fasting bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 18 publications
6
29
3
2
Order By: Relevance
“…In this study, more females have Type 2 diabetes compared to male which was found to be statistically significant, whereas, in the WHO report in southeast Asia, more male diabetics have been observed. [2] Several studies showed increased risk of diabetes with positive family history of diabetes, [14,20,21] but in the present study, there was no significant association between family history of diabetes and RBS level this may be due to majority of study participants parents or siblings were not screened for diabetes and awareness about screening for diabetics was found to be poor.…”
Section: Discussioncontrasting
confidence: 55%
“…In this study, more females have Type 2 diabetes compared to male which was found to be statistically significant, whereas, in the WHO report in southeast Asia, more male diabetics have been observed. [2] Several studies showed increased risk of diabetes with positive family history of diabetes, [14,20,21] but in the present study, there was no significant association between family history of diabetes and RBS level this may be due to majority of study participants parents or siblings were not screened for diabetes and awareness about screening for diabetics was found to be poor.…”
Section: Discussioncontrasting
confidence: 55%
“…The family history of specific diseases reflects the consequences of genetic susceptibility, shared environment and common behaviors [23]. The area of residence has an effect on the level of metabolic control, the occurrence of diabetic complications, and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 31 % of diabetic patients were having MS. An earlier study had found that 62 % of newly diagnosed T2DM patients were having MS according to IDF criteria [34] and it has also been suggested that family history of T2DM can be useful predictor for diagnosis of MS [35]. It is known that impaired fasting glucose is a risk factor for diabetes and both are known to be associated closely with obesity, though the mechanism behind this is not confirmed yet [36].…”
Section: Discussionmentioning
confidence: 99%